2019
DOI: 10.1371/journal.pone.0213998
|View full text |Cite
|
Sign up to set email alerts
|

The variation of the burden of hypertension and diabetes in two large districts of the city of São Paulo, Brazil, based on primary health care routinely-collected data

Abstract: BackgroundNoncommunicable diseases (NCDs) were responsible for 72.3% of global deaths in 2016, with cardiovascular diseases accounting for almost half of those deaths and low- and middle-income countries carrying the biggest burden. As a result, the prevention and control of NCDs is recognized as urgent, while better surveillance at the country level could result in more effective policies. Hence, the objective of this study was to obtain more detailed information on the distribution of the prevalence of hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Although the prevalence of self-reported DM in different surveys [11][12][13][14] and measured by the PNS, when considering HbA1c ≥ 6.5% 10 , is higher among women, this study found no differences in the frequency of prediabetes/intermediate hyperglycemia by gender, in agreement with the results of the IDF 6 . On the other hand, the pattern observed increased prevalence according to the population's age, with a risk gradient given by low schooling, obesity, and comorbidities such as arterial hypertension, besides physical inactivity, is per the occurrence of diabetes itself [10][11][12] .…”
Section: Discussionsupporting
confidence: 82%
“…Although the prevalence of self-reported DM in different surveys [11][12][13][14] and measured by the PNS, when considering HbA1c ≥ 6.5% 10 , is higher among women, this study found no differences in the frequency of prediabetes/intermediate hyperglycemia by gender, in agreement with the results of the IDF 6 . On the other hand, the pattern observed increased prevalence according to the population's age, with a risk gradient given by low schooling, obesity, and comorbidities such as arterial hypertension, besides physical inactivity, is per the occurrence of diabetes itself [10][11][12] .…”
Section: Discussionsupporting
confidence: 82%
“…The decision to engage with Brazil was based on several criteria: first, the characteristics of the healthcare system-Brazil has a public health system [31] that recognizes health as a universal constitutional right, provides access to medicines [32] and vests the responsibility to execute primary care delivery at the municipal level. Second, the burden of hypertension in São Paulo is high and is increasing [33], and the health system faces burgeoning pressures in the face of urbanization, a double disease burden where NCDs overtake communicable diseases, and political interference. It is understood that there remains ample opportunity to make greater use of known evidence-based practices for reducing hypertension in resource-constrained settings [29], despite documented improvements in hypertension diagnosis and management across several geographies [34].…”
Section: An Evidence-building Opportunity: Design Thinking and The Be...mentioning
confidence: 99%